Design and Analysis of Impeller for Ducted Axial-flow Turbine in Natural Gas Power Generation Systems - Gao, Dongming; Zhang, Ran; Wu, Lide; Fan, Hua (International Journal of Mechanical and Electrical Engineering, 2026)
Natural gas pressure difference power generation is an innovative low-carbon energy technology that integrates energy efficiency, environmental protection, and economic benefits. This paper proposes a ducted natural gas pressure energy power generation device using an axial-flow turbine. The geometric parameters of the rotor and stator blades of the axial-flow turbine are derived through a one-dimensional design method. Additionally, the flow characteristics and blade load distribution of this blade profile are analyzed, and directions for further optimizing the turbine to enhance its output power are put forward.